Reconsidering Polygamy Law Through The Lens Of Substantive Justice: A Critical Analysis Of Islamic Family Law In Indonesia - Adang Djumhur Salikin (Ann Publisher, 2026)
Background. The urgency of this research lies in the persistent gap between normative legal provisions and the lived experiences of justice among women in polygamous marriages, as evidenced by mounting empirical data on economic disenfranchisement, psychological distress, and social stigmatization. Aims. This article aims to critically examine polygamy law in Indonesia not merely from a legal-formal perspective but through the lens of substantive justice. It seeks to answer whether polygamy regulations (Marriage Law No. 1/1974 and the Compilation of Islamic Law) have produced tangible justice for all affected parties, particularly women and children, or merely serve as administrative procedures that legitimize patriarchal practices. Methods. This research employs normative legal research with philosophical, statutory, and comparative approaches. The analysis draws upon substantive justice theories from critical legal studies and legal philosophy—particularly Gustav Radbruch's triadic theory of law (justice, certainty, utility), Satjipto Rahardjo's Progressive Law, and Asghar Ali Engineer's theory of substantive justice for the weak—as analytical tools to examine polygamy provisions and their implementation in Religious Courts. Result. This research reveals a fundamental disparity between legal texts and the reality of justice. First, polygamy regulations (Articles 4 and 5 of Marriage Law No. 1/1974) remain highly procedural and have not addressed psychological and social justice dimensions for wives and children. The requirement of